PERKAWINAN BEDA AGAMA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 68/ PUU-XII/2014 DALAM PERSPERKTIF HAM - Setiyanto, Danu Aris (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Interfaith marriage, in fact, is a contentious issue in the family law. The arrangement of interfaith marriage in Indonesia is experiencing a change since before and after the establishment of the constitutional Law of R.I. No. 1 of 1974 regarding Marriage. Although there are changes in the regulations but some parties consider that arrangement of interfaith marriage is not firm, it is unclear / smuggling law in it. Regulation of interfaith marriage in Indonesia is considered to have reduced the freedom to choose a mate and find the happiness with a partner of different religions. This is considered by the applicant that Article 2, paragraph 1 does not comply with the principle of freedom of human rights. This paper focuses on studying the problems of the interfaith marriages after a Constitutional Court decision No. 68 / PUU-XII / 2014 in the perspective of human rights. Constitutional Court rejected entirely about judicial interfaith marriage, as it is considered unreasonable under the law and marriage in Indonesia is based on religion. Constitutional Court's decision contains the values of human rights with a particular meaning and is limited by the limited freedom of religion in Pancasila and the 1945 Constitution.[Perkawinan beda agama secara fakta merupakan persoalan yang menjadi perdebatan dalam hukum keluarga. Pengaturan perkawinan beda agama di Indonesia mengalami perubahan sejak sebelum dan setelah adanya UU R.I. Nomor 1 tahun 1974 tentang Perkawinan. Walaupun ada perubahan secara regulasi tetapi beberapa pihak menganggap bahwa pengaturan perkawinan beda agama tidak tegas, ada ketidakjelasan/penyelundupan hukum di dalamnya. Regulasi perkawinan beda agama di Indonesia dianggap telah mengurangi kebebasan untuk memilih jodoh dan menemukan kebahagiaan bersama pasangannya yang berbeda agama. Hal inilah yang dianggap oleh para pemohon bahwa Pasal 2 ayat 1 tidak sesuai dengan prinsip kebebasan dalam HAM. Tulisan ini difokuskan untuk mengkaji permasalahan perkawinan beda agama pasca putusan Mahkamah Konstitusi Nomor 68/ PUU-XII/2014 dalam perspektif HAM. Mahkamah Konstitusi menolak seluruhnya tentang uji materiil perkawinan beda agama, karena dinilai tidak beralasan menurut hukum dan perkawinan di Indonesia yang berdasarkan agama. Putusan MK mengandung nilai-nilai HAM yang bermakna partikular dengan kebebasan terbatas dan dibatasi oleh agama dalam Pancasila dan UUD 1945]